Macrophage-Mediated Dorsal Root Ganglion Damage Precedes Altered Nerve Conduction in SIV-Infected Macaques - Laast, Victoria A. (American Society for Investigative Pathology, 2011)
Peripheral neuropathy is the most common neurological complication of HIV-1 infection, affecting over one-third of infected individuals, including those treated with antiretroviral therapy. To study the pathogenesis of HIV-induced peripheral nervous system disease, we established a model in which SIV-infected macaques developed changes closely resembling alterations reported in components of the sensory pathway in HIV-infected individuals. Significant declines in epidermal nerve fiber density developed in SIV-infected macaques, similar to that of HIV-infected individuals with neuropathy. Changes in dorsal root ganglia (DRG) included macrophage infiltration, SIV replication in macrophages, immune activation of satellite cells, and neuronal loss. To determine whether dorsal root ganglion damage was associated with altered nerve function, we measured unmyelinated C-fiber conduction velocities (CV) in nerves of SIV-infected macaques and compared CV changes with DRG alterations. Twelve weeks postinoculation, SIV-infected macaques had significantly lower C-fiber conduction velocity in sural nerves than uninfected animals and the magnitude of conduction velocity decline correlated strongly with extent of DRG macrophage infiltration. Thus, injury to neurons in the DRG—mediated by activated macrophages—preceded altered conduction of unmyelinated nerve fibers in SIV-infected macaques, suggesting that macrophage-mediated DRG damage may be the initiating event in HIV-induced sensory neuropathy.